Serum Antibodies Against the E5 Oncoprotein from Human Papillomavirus Type 16 Are Inversely Associated with the Infection and the Degree of Cervical Lesions - Azucena Salazar-Piña; Minerva Maldonado-Gama; Ana M. Gonzalez-Jaimes; Aurelio Cruz-Valdez; Eduardo Ortiz-Panozo; Fernando Esquivel-Guadarrama; Lourdes Gutierrez-Xicotencatl (Biomedicines)
Background: The humoral immune response against human papillomavirus (HPV) has been suggested as a source of biomarkers for the early detection of cervical cancer (CC). Therefore, we aimed to characterize the antibody response against HPV16 E5 in the natural history of cervical cancer and to determine its usefulness as a biomarker of HPV-associated cervical lesions. Methods: This study was conducted at the Cuautla General Hospital, Morelos, Mexico, with women (18 to 64 years) who agreed to participate. Samples were obtained from 335 women with cervical lesions and 150 women with negative Papanicolaou tests. HPV genotyping was performed by PCR and pyrosequencing, and anti-E5 antibodies were detected by slot blot. Results: The overall anti-E5 antibodies prevalence in the study was 17.9%, with the higher prevalence observed in the no lesion (NL, 49.4%) group, and with a downward trend according to the degree of the cervical lesion, from cervical intraepithelial neoplasia-1 (CIN1, 32.2%) to CIN2 (11.5%) and CIN3/CC (6.9%). The logistic regression model showed negative associations of anti-E5 antibodies with CIN1 (OR = 0.38), CIN2 (OR = 0.42), and CIN3/CC (OR = 0.32) groups, being statistically significant. Contrast analysis showed an inverse relationship between anti-E5 antibodies with HPV DNA and the CIN1 (OR = 0.35), CIN2 (OR = 0.39), and CIN3/CC (OR = 0.31) groups. Conclusions: These results suggest that anti-E5 antibodies could be associated with clearance of infection in women without lesions and with CIN1 lesions since an inverse relationship was observed between the presence of HPV DNA and anti-E5 antibodies. In contrast, with progression from CIN2/CIN3 to CC, the relationship was reversed, as the anti-E5 antibodies disappeared, and the frequency of the viral genome increased.